Interaktive sozialgeographie - Schaffer, Franz (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1997)
The theoretical and methodological aspects are discussed, of social geography which is oriented into the finding of developmental potentials, and adapted to the needs of practice.
Keywords: družbena geografija; geografija; geography; human geography; metode; metodologija; raziskovalno delo; znanstvenoraziskovalno delo